Letusan Gunung dan Persepsi Sang Pujangga: Kesaksian Teks Bima, Jawa, dan Melayu Abad ke-19 - Sudibyo, Sudibyo (Manuskripta, 2019)
This article aims to describe manuscript comparison between Syair Nabi Allah Ayub (SNAA) and Hikayat Nabi Ayub Dimurkai Allah (HNADA) based on intertextual approach. This study describes equations, differences and hypograms in the form of expansion and modification. The equation in the two texts is that the Prophet Ayub was given a trial repeatedly by Allah SWT, the Prophet Ayub left his country when he was sick, the wife of the Prophet Job made a living when the Prophet Ayub was sick, Prophet Ayub recovered thanks to the water rising from the ground. The difference in the two texts is the beginning of the story of Prophet Job, the background of the story and the end of the story. The expansion hypogram is in the form of the addition of the angel Michael's figure and the reduction of the male character to the SNAA script. The conversion in the form of SNAA text seems to be a predecessor text of HNADA because it has a more complete story, even though the year of writing was older. While the modification is a change because the Prophet Ayub received trials from God. === Tulisan ini bertujuan untuk mengungkap persepsi pujangga tentang sifat destruktif gunung terutama dalam teks-teks abad ke-19, utamanya dalam Syair Kerajaan Bima (SKB), Babad Betawi (BB), Babad Diponegoro (BD), dan Syair Lampung Karam (SLK).